Power management strategies for microgrids - Jiao, Jianting (2012)
Human consumption of traditional fossil fuel is the main factor of global warming. The situation now for all mankind is much more serious than ever before. With the crisis of fossil fuel, hunting for new energy sources is one of the primary tasks for all human being. A microgrid is one of the solution for energy crisis which integrate distributed generation and distribution system consisting of a medium/low voltage distribution network with distributed energy resources (such as solar PV, fuel cells, wind turbines and energy storage devices), local loads and power electronic converters operated either grid-connected or islanded mode.